Teacher language awareness - Andrews, Stephen (Cambridge University Press, 2007)
TTeacher Language Awareness (TLA) is an area of increasing interest to those involved in language teacher education. This book provides an introduction to the nature of TLA, assesses its impact upon teaching and its potential impact on learning. The book focuses specifically on grammar. It aims to encourage teachers and others involved in language education to think more deeply about the importance of TLA ad to adopt a more principled approach to the planning of those parts of their programmes assosciated with it.